2021
DOI: 10.1101/2021.05.27.21257936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inference of SARS-CoV-2 generation times using UK household data

Abstract: The distribution of the generation time (the interval between individuals becoming infected and passing on the virus) characterises changes in the transmission risk during SARS-CoV-2 infections. Inferring the generation time distribution is essential to plan and assess public health measures. We previously developed a mechanistic approach for estimating the generation time, which provided an improved fit to SARS-CoV-2 data from January-March 2020 compared to existing models. However, few estimates of the gener… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In this model, each infection is divided into three successive stages (the duration of time in each stage followed independent distributions): latent, presymptomatic and infectious, and symptomatic and infectious. 17 , 18 Unlike standard methods for estimating the generation time, 15 , 16 this approach links an infected host's infectivity profile to the time at which they develop symptoms .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this model, each infection is divided into three successive stages (the duration of time in each stage followed independent distributions): latent, presymptomatic and infectious, and symptomatic and infectious. 17 , 18 Unlike standard methods for estimating the generation time, 15 , 16 this approach links an infected host's infectivity profile to the time at which they develop symptoms .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have estimated the SARS-CoV-2 generation time, 15 , 16 , 17 , 18 , 19 , 20 with most estimates using data collected early in the COVID-19 pandemic. A household study 18 from the UK Health Security Agency (UKHSA) indicated that the generation time of SARS-CoV-2 became shorter between September and November, 2020, compared with the earlier months.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of G, the time period considered as measured in mean generation times, is going to be a subjective decision. Estimates for the generation time are variable between studies, but typically around 4-6 days [34][35][36]. We take G = 15 by default, corresponding to a time window of two to three months.…”
Section: Parametrizationmentioning
confidence: 99%